2016
DOI: 10.1007/s40271-016-0167-y
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Medicaid Expansion from the Perspective of Patient Experience in Hospitals

Abstract: Hospitals serving higher concentrations of Medicaid patients and more racial/ethnic diverse patients experienced a less satisfactory patient experience than patients utilizing other payers or patients who were White. Our research magnifies the challenge for addressing the disparities that exist in healthcare. Further research is called for clarifying the underlying reasons for these disparities and the optimal strategies for addressing these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…This suggests that financially strained hospitals that are able to substantially reduce higher than average levels of uncompensated care may see meaningful improvements in patient experience scores. This is in accordance with the literature examining the relationship between financial security and hospital quality, with evidence suggesting that quality is most affected in hospitals with deep financial problems …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This suggests that financially strained hospitals that are able to substantially reduce higher than average levels of uncompensated care may see meaningful improvements in patient experience scores. This is in accordance with the literature examining the relationship between financial security and hospital quality, with evidence suggesting that quality is most affected in hospitals with deep financial problems …”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with the literature examining the relationship between financial security and hospital quality,[25][26][27][28][29][30][31][32] with evidence suggesting that quality is most affected in hospitals with deep financial problems 14. Understanding the relationship between hospital financesand patient outcomes is particularly important in the context of federal funding cuts to safety-net hospitals and new valuebased reimbursement models precipitated by the ACA.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The low scores by Medicaid patients are consistent with other studies, 8,10,12,13 including one done by Liu, et al that found hospitals with more Medicaid patients received lower patient satisfaction scores. 14 Medicaid often covers the most vulnerable and disadvantaged patients.…”
Section: Discussionmentioning
confidence: 99%